DESCRIPTION OF TRIGLYCERIDE LEVELS IN ALCOHOL CONSUMERS IN TIBAWA DISTRICT GORONTALO REGENCY - Ilham Rizki Bolota; Erfan AR. Lainjong; Rachma (Journal of Health, Technology and Science (JHTS), 2026)
Alcohol consumption is known to influence lipid metabolism and may contribute to elevated triglyceride levels, which are associated with an increased risk of cardiovascular disease, pancreatitis, and other metabolic disorders. This study aimed to describe triglyceride levels among alcohol consumers in Tibawa District, Gorontalo Regency. A quantitative descriptive study with a cross-sectional approach was conducted from July to August 2025. The study involved 30 alcohol consumers selected using purposive sampling. Venous blood samples were collected and analyzed using an enzymatic colorimetric method with a spectrophotometer to determine serum triglyceride levels. Data were analyzed descriptively using frequencies, percentages, means, minimum values, and maximum values. The results showed that most respondents were male (66.7%) and aged 10–18 years (63.3%). Triglyceride examination revealed that 29 respondents (96.7%) had normal triglyceride levels, while only 1 respondent (3.3%) had abnormal triglyceride levels. The mean triglyceride level was 141.70 ± 28.99 mg/dL, with a minimum value of 105 mg/dL and a maximum value of 215 mg/dL. These findings indicate that the majority of alcohol consumers in Tibawa District had triglyceride levels within the normal range, although abnormal triglyceride levels were identified in a small proportion of respondents. Continuous health education and monitoring are recommended to prevent future lipid metabolism disorders associated with alcohol consumption.